An efficient asymmetric synthesis of (-)-lupinine. - Davies, S; Fletcher, A; Foster, E; Houlsby, I; Roberts, P; Schofield, T; Thomson, J (Royal Society of Chemistry, 2014)
The asymmetric synthesis of (-)-lupinine was achieved in 8 steps, 15% overall yield and >99 : 1 dr from commercially available starting materials. The strategy used for the construction of the quinolizidine scaffold involved reaction of an enantiopure tertiary dibenzylamine via two sequential ring-closures which both occurred with concomitant N-debenzylation.